Charting a path for prioritization of novel agents for clinical trials in osteosarcoma: A report from the Children's Oncology Group New Agents for Osteosarcoma Task Force. Issue 9 (16th June 2021) - Whittle, Sarah B.; Offer, Katharine; Roberts, Ryan D.; LeBlanc, Amy; London, Cheryl; Majzner, Robbie G.; Huang, Alex Y.; Houghton, Peter; Alejandro Sweet Cordero, E.; Grohar, Patrick J.; Isakoff, Michael; Bishop, Michael W.; et al.
Abstract: Osteosarcoma is the most common bone tumor in children and young adults. Metastatic and relapsed disease confer poor prognosis, and there have been no improvements in outcomes for several decades. The disease's biological complexity, lack of drugs developed specifically for osteosarcoma, imperfect preclinical models, and limits of existing clinical trial designs have contributed to lack of progress. The Children's Oncology Group Bone Tumor Committee established the New Agents for Osteosarcoma Task Force to identify and prioritize agents for inclusion in clinical trials. The group identified multitargeted tyrosine kinase inhibitors, immunotherapies targeting B7‐H3, CD47‐SIRPα inhibitors, telaglenastat, and epigenetic modifiers as the top agents of interest. Only multitargeted tyrosine kinase inhibitors met all criteria for frontline evaluation and have already been incorporated into an upcoming phase III study concept. The task force will continue to reassess identified agents of interest as new data become available and evaluate novel agents using this method.